WEBSITE HIV/AIDS BAGI KADER DI PIMPINAN RANTING ‘AISYIYAH BALECATUR YOGYAKARTA - Astuti, Dhesi Ari; Kurniati, Nurul; Ardina, Mega; Rasyid, Erwin (Community Services and Social Work Bulletin, 2023)
The incidence of HIV / AIDS in Sleman Regency is still a health problem that must get attention, although the numbers have decreased, this is because HIV AIDS is still an undiagnosed iceberg phenomenon because tracing and testing processes are not carried out in all at-risk groups, especially now that the Covid-19 pandemic is a major concern in the health sector. The Covid-19 pandemic has caused the activities of mobile cadres in socialization or educational services to be hampered and even stopped because they follow the rules to comply with health protocols to prevent transmission of the coronavirus. Promotive and preventive efforts as a solution to problems are important to be implemented, namely providing HIV/AIDS prevention education to various stakeholders in Ngaran Hamlet and involving HIV AIDS cadres who have been formed through the Aisyiyah Balecatur branch management which is considered to have a risk for Ngaran, and providing an HIV/AIDS website platform.